Physiological activity of a bioluminescent Pseudomonas fluorescens (strain 2–79) in the rhizosphere of mycorrhizal and non-mycorrhizal pepper ( Capsicum annuum L.) - Marschner, Petra; Crowley, David E. (Soil biology & biochemistry, 1996)
Physiological status and root-colonization of Pseudomonas fluorescens 2–79RL were examined in presence or absence of mycorrhizae on the roots of pepper over 6 weeks. Due to incorporation of a ribosomal promoter-driven lux marker into the chromosome of this bacterium, the end of the lag phase and onset of exponential growth is marked by an exponential increase in bioluminescence. In vitro, the duration of the lag phase of bioluminescence after transfer of cells to rich medium increased when the cells had been grown under low nutrient conditions or subjected to prolonged starvation. Lag phase duration thus provided a marker for assessment of changes in the physiological status of P. fluorescens 2–79RL. Pepper plants, non-mycorrhizal or mycorrhizal with Glomus intraradices (GI) or Glomus deserticulum (GD), were grown for 42 days in microcosms containing soil inoculated with P. fluorescens 2–79RL. A blotting technique using filter paper strips was developed to sample cells from the rhizosphere, after which the cells were resuspended for enumeration and determination of lag phase duration. During the first 3 weeks, the population density of P. fluorescens 2–79RL (cfu mm −2) decreased by one order of magnitude on the roots and by two orders of magnitude in the bulk soil. The lag phase of bioluminescence remained stable during the first 20 days in the rhizosphere and the bulk soil, but then increased up to day 27 and remained at the higher level until day 38. The length of the lag phase was greater in the bulk soil than in the rhizosphere. Compared with the non-mycorrhizal plants, mycorrhizal infection by GD significantly decreased shoot dry weight and the population of P. fluorescens 2–79RL in the rhizosphere at the root tip and on the older root parts. GD also significantly increased the length of the lag phase of bioluminescence on the older root parts. The effect of GI was less pronounced. The results show this bacterium may be subject to moderate to severe starvation in the rhizosphere and that there are differential effects of specific mycorrhizal fungi on both the population and activity of this root-colonizing pseudomonad.